2017
DOI: 10.1007/s10488-017-0796-z
|View full text |Cite
|
Sign up to set email alerts
|

The Juggling Act of Supervision in Community Mental Health: Implications for Supporting Evidence-Based Treatment

Abstract: Supervisors are an underutilized resource for supporting evidence-based treatments (EBT) in community mental health. Little is known about how EBT-trained supervisors use supervision time. Primary aims were to describe supervision (e.g., modality, frequency), examine functions of individual supervision, and examine factors associated with time allocation to supervision functions. Results from 56 supervisors and 207 clinicians from 25 organizations indicate high prevalence of individual supervision, often along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…Although it does not reduce the amount of resources required, Bearman et al (2013) describe strategies that may optimize supervision and increase the likelihood that activities discussed in supervision will actually be implemented in practice. Although more work is needed to understand the best strategies for supervision/consultation, Dorsey, Pullmann, et al (2017) have identified the importance of implementation climate as one predictor of the amount of time dedicated to clinical and EBT-related discussions in supervision.…”
Section: Resource Intensivementioning
confidence: 99%
“…Although it does not reduce the amount of resources required, Bearman et al (2013) describe strategies that may optimize supervision and increase the likelihood that activities discussed in supervision will actually be implemented in practice. Although more work is needed to understand the best strategies for supervision/consultation, Dorsey, Pullmann, et al (2017) have identified the importance of implementation climate as one predictor of the amount of time dedicated to clinical and EBT-related discussions in supervision.…”
Section: Resource Intensivementioning
confidence: 99%
“…The extent to which supervisory alliance is a relevant and important construct in supporting the implementation of evidence-based psychosocial interventions is largely unstudied. Research has focused more on clinical supervision, including techniques used by expert consultants (e.g., Bearman et al 2013, 2016) and content of supervision (Accurso et al 2011; Dorsey et al 2017). In public mental health, supervisors often have both clinical, administrative and managerial responsibilities, with about 20–30% of supervision focused on administrative and other non-clinical functions (Accurso et al 2011; Dorsey et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research has focused more on clinical supervision, including techniques used by expert consultants (e.g., Bearman et al 2013, 2016) and content of supervision (Accurso et al 2011; Dorsey et al 2017). In public mental health, supervisors often have both clinical, administrative and managerial responsibilities, with about 20–30% of supervision focused on administrative and other non-clinical functions (Accurso et al 2011; Dorsey et al 2017). While ongoing supervision appears to be necessary in the successful implementation of evidence-based treatments (EBTs; Beidas and Kendall 2010; Herschell et al 2010; Schoenwald et al 2013), the supervisory working relationship has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace-based supervision includes both clinical supervision as well as oversight for administrative issues, professional development, and emotional support, provided by internal staff employed within an organization ( 18 ). In a study by our research group examining workplace-based supervision within organizations participating in a state-funded EBT initiative, weekly occurrence of supervision was mostly upheld [75% reported weekly supervision for ~1 h ( 19 )].…”
Section: Introductionmentioning
confidence: 99%